PENGARUH KUALITAS AUDIT DAN KUALITAS PELAYANAN PADA KEPUASAN KLIEN KANTOR AKUNTAN PUBLIK DI BALI - Suindari, Ni Made; Suardikha, I Made Sadha; Ratnadi, Ni Made Dwi (Buletin Studi Ekonomi; VOL.22.NO.1. FEBRUARI 2017 (PP 1-112), 2017)
The study is aimed to analyze the influence of audit quality and service quality toward the client satisfaction at the audit firms in Bali. The study was conducted at the company that became the audit client of audit firm in Bali for the end year 2015 by using primary data obtained from questionnaires. Method of sampling is convenience sampling and obtained samples of 156 companies. The questionnaire can be used 81 questionnaires. Data analysis is done by multiple regression analysis model. The result showed the audit quality and service quality has positive effect toward the client satisfaction. This indicates that client satisfaction of audit firm in Bali is not only affected by technical competence and independent of auditors, but also affected by quality of the service from marketing aspects.